Percepção e representação da morte nas paisagens arqueológicas de São Cristóvão e Laranjeiras - Bonjardim, Solimar Guindo Messias (2009)
The purpose of the current study is to evaluate the territories of the death under the perspective of the perception of residents and frequent visitors of catholic temples from the towns of Laranjeiras and São Cristóvão during the eighteenth century. Therefore, the changes involved with the relation of the society with death were analyzed and, hence, the initial assumption is that the death had drawn the dominant landscape in the towns owing to its direct relationship with the churches-cemeteries. In the current days, towns presenting this sort of landscape, such as São Cristóvão and Laranjeiras in Sergipe, are possible targets of archeological studies. By analyzing the remainder death landscapes in these towns, it is realized how present in the quotidian of people the death was, drawing a different landscape in the current times, once as time gone by, the rituals have gone through changes. These towns shelter a considerable number of churches with gravestones inside and, sometimes,cemeteries outside. Thus, it was evidenced that the sacred spaces of the towns still cover the death territory, notwithstanding a new territory, with new symbols and representations. The pre-existing territory of the death, which had drawn the current archeological landscapes, is now perceived as part of a past that, once considered re-signified history, conceals its own signification. Ultimately, it was verified the existence not simply of a death territory, but also an overlapping of death multi-territories, foe every time a space-territory dissociation is processed, a new space-representation connection is established, revealing a new territory of the death